2008
DOI: 10.4319/lo.2008.53.3.1054
|View full text |Cite
|
Sign up to set email alerts
|

Sources and transport of terrestrial organic matter in Vancouver Island fjords and the Vancouver‐Washington Margin: A multiproxy approach using d13Corg, lignin phenols, and the ether lipid BIT index

Abstract: The Branched and Isoprenoid Tetraether (BIT) index (a ratio of marine and terrestrial glycerol dialkyl glycerol tetraether [GDGT] membrane lipids) was recently introduced as a proxy for the fraction of fluvially derived organic carbon (OC) buried in marine sediments. We investigate the source and distribution of terrestrial OC in marine sediments in a large spatial data set that encompasses the Washington-Vancouver Island Margin, Vancouver Island fjords, and Puget Sound with the goal of comparing the BIT index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 32 publications
6
121
3
3
Order By: Relevance
“…When archaeal lipids are of particular interest, the phosphate buffer is followed by a trichloroacetic acid extraction (TCA) (Nishihara and Koga 1987;Sturt et al 2004;Lipp et al 2008). However, most GDGT studies to date have not explicitly aimed to investigate intact lipids and instead use ASE or sonic extraction of environmental samples followed by analysis of core lipids with no hydrolysis step (e.g., Schouten et al 2002;Huguet et al 2006aHuguet et al , 2007aKim et al 2007;Walsh et al 2008). This study shows that both M-B-Dyer and ASE are inferior methods for extracting I-GDGT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When archaeal lipids are of particular interest, the phosphate buffer is followed by a trichloroacetic acid extraction (TCA) (Nishihara and Koga 1987;Sturt et al 2004;Lipp et al 2008). However, most GDGT studies to date have not explicitly aimed to investigate intact lipids and instead use ASE or sonic extraction of environmental samples followed by analysis of core lipids with no hydrolysis step (e.g., Schouten et al 2002;Huguet et al 2006aHuguet et al , 2007aKim et al 2007;Walsh et al 2008). This study shows that both M-B-Dyer and ASE are inferior methods for extracting I-GDGT.…”
Section: Discussionmentioning
confidence: 99%
“…We searched the literature for GDGT extraction methods and measured the efficiency and degree of polar head group loss for each method using a culture of exponentially growing N. maritimus that contained only I-GDGTs. We then analyzed samples from environments where GDGT-based proxies are commonly measured, including marine water column particles, marine sediments, and soils.We evaluated five basic techniques: solvent extraction with mild acid to enhance the lyses of archaeal cells (e.g., Bligh and Dyer 1959;Nishihara and Koga 1987), accelerated solvent extraction (ASE) (e.g., Huguet et al 2007b; Kim et al 2008), solvent extraction with sonication (e.g., Schouten et al 2002;Huguet et al 2006a;Walsh et al 2008), soxhlet extraction (e.g., Turich et al 2007;Pancost et al 2008), and sample saponification (e.g., Wakeham et al 2003;. Acidified solvent extraction, especially after an initial extraction with phosphate buffer (modified Bligh-Dyer) is considered to be superior for living biomass (Bligh and Dyer 1959;Sturt et al 2004;Lipp et al 2008), whereas ASE is traditionally used in sediments and soils where most GDGT proxy records are measured.…”
mentioning
confidence: 99%
“…Subsequently, since brGDGTs occur ubiquitously in soils (Weijers et al, 2006b) and because brGDGTs are not associated with fresh higher plant debris (Walsh et al, 2008), it is interpreted as a tracer of soil OC (e.g., Huguet et al, 2007;Weijers et al, 2009). In the case of the Tagus River basin, we found that the brGDGTs in the river are not only derived from soils but also produced in situ, in line with other recent studies of river systems (Zell et al, 2013a, b;De Jonge et al, 2014).…”
Section: Bit Indexmentioning
confidence: 99%
“…In addition to the TEX 86 , the BIT (Branched Isoprenoid Tetraether) index (Hopmans et al, 2004) can be derived from GDGT analyses that include the soil derived branched tetraether lipids (Hopmans et al, 2004). The BIT index is used as an indicator for the relative contribution of soil organic matter (Kim et al, 2006;Weijers et al, 2006;Walsh et al, 2008) transported into the Red Sea in the past. Today, the surrounding desert conditions and the lack of large rivers draining into the basin do not suggest a large input of soil derived GDGTs, as shown by low BIT values (<0.1) in the Red Sea surface sediments .…”
Section: Methodsmentioning
confidence: 99%